2010
DOI: 10.1016/j.juro.2010.05.016
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Renal Function in Children Undergoing Extracorporeal Shock Wave Lithotripsy

Abstract: Shock wave lithotripsy is a safe modality for treating renal calculous disease in children up to 16 years old, with no impact on long-term kidney function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 23 publications
0
16
0
Order By: Relevance
“…8 ± 3.5/yr 84.6 ± 24.7 82.5 ± 26.5 0.33 Fayad et al [27] 100 Children 6 mo 113.13 ± 4.51 113.01 ± 4.27 0.46…”
Section: Percutaneous Nephrolithotomymentioning
confidence: 98%
See 1 more Smart Citation
“…8 ± 3.5/yr 84.6 ± 24.7 82.5 ± 26.5 0.33 Fayad et al [27] 100 Children 6 mo 113.13 ± 4.51 113.01 ± 4.27 0.46…”
Section: Percutaneous Nephrolithotomymentioning
confidence: 98%
“…In contrast, it is stated that serum creatinine levels were not markedly affected after SWL in patients with a solitary kidney in approximately 4 years follow up [26] . In addition, it is stated that SWL treatment was not associated with a significant impact on kidney function or subsequent renal scaring, regardless of stone size or number of SWL seances in children [27] . The results of these two studies are shown in (Table 1).…”
Section: Extracorporeal Swlmentioning
confidence: 99%
“…In children, SWL has a major role in the treatment of urinary stone disease [3] . SWL is not related to decreases in kidney function or subsequent renal scarring [4] . Pretreatment with ureteral stent placements in the pediatric population is still a debated issue.…”
Section: Introductionmentioning
confidence: 83%
“…The patient should not move during ESWL. When the child is not old enough to understand our instructions, general anesthesia is needed (1.5 mg/kg ketamine and 0.05 mg/kg midazolam are preferred) 18. Small children also may need some suspension under the body, and the water cushion also should be adjusted.…”
Section: Methodsmentioning
confidence: 99%